The Polyphony of English Studies A Festschrift for Allan James - Onysko, Alexander 1974-; Graf, Eva-Maria 1969-; Delanoy, Werner 1958-; Dobrić, Nikola 1982- (Gunter Narr Verlag, 2017)
This volume, in honor of Allan James, collects a range of articles from different domains of English studies as a token of Allan James's academic interests and his integrative approach to the field. The contributions in linguistics encompass a spectrum of topics including world Englishes, professional discourse, language acquisition, collocation, translation, and multilingualism. Cultural aspects in language teaching and in literary analysis enrich the reading and hint at Allan James' Welsh and Celtic roots while also going beyond that
[1. Auflage]
Keywords: English Studies; Linguistics; Literatur